Meningkatkan Hasil Belajar IPA Menggunakan Model Project Team di Kelas 5 Sekolah Dasar - Nadia; Mahmuddin (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in learning science in grade 5 UPTD SDN 2 Kait-Kait is the lack of student activity and student learning outcomes. This is because learning is still one-way, learning tends to be boring and less interesting and the learning atmosphere is less pleasant. Thus, it is necessary to innovate learning by combining several learning models into the Project Team learning model. The purpose of this study is to analyze how student activity and analyze the improvement of student learning outcomes. This research uses a qualitative approach with the type of Classroom Action Research (PTK) which is carried out in 3 meetings. The results showed that student activity reached a percentage of 92% with the criteria of "Very Active" and student learning outcomes also increased with classical completeness reaching 88% of students who were completed. Based on the results of classroom action research that has been carried out on grade 5 students of UPTD SDN 2 Kait-Kait Tanah Laut it can be concluded that by applying a combination of Project Team models in science learning can improve student activity and student learning outcomes.